Comparison of community structure of the epigaeic invertebrate fauna, with particular reference to ants and beetles, between fynbos sites under different management practices - Donnelly, Diane (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1983.